2008
DOI: 10.1007/s10668-008-9153-4
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of international scientific cooperation in fisheries, aquaculture and coastal zones: some preliminary lessons

Abstract: The paper examines preliminary experiences with international scientific cooperation in fisheries, aquaculture and coastal zone issues through 90 projects in successive European Research Framework Programmes (FP4-FP6: 1994-2006. FPs had increasingly ambitious objectives in response to international commitments, such as the Convention on Biological Diversity, the Millennium Development Goals, the Johannesburg Plan of Implementation and dialogue with partner regions. Sustainable aquatic food production in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Research collaboration improves the quality and quantity of research output, as well as the visibility of national health problems [69][70][71][72]. Furthermore, international collaboration in research helps in capacity building in developing countries and makes national problems of developing countries more observable [73]. Arab researchers need to take the lead and promote research projects in the field of infectious diseases as an important public health concern.…”
Section: Discussionmentioning
confidence: 99%
“…Research collaboration improves the quality and quantity of research output, as well as the visibility of national health problems [69][70][71][72]. Furthermore, international collaboration in research helps in capacity building in developing countries and makes national problems of developing countries more observable [73]. Arab researchers need to take the lead and promote research projects in the field of infectious diseases as an important public health concern.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies indicated that international collaboration can increase the visibility of scientific publication from a particular country [64]. Furthermore, international collaboration in research helps in capacity building in developing countries and make national problems of developing countries more observable [65]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies indicated that international collaboration can increase the visibility of scientific publications from a particular country [ 40 ]. Furthermore, international collaboration in research helps capacity building in developing countries and makes national problems of developing countries more observable [ 41 ].…”
Section: Discussionmentioning
confidence: 99%